2016
DOI: 10.1177/1753425916631032
|View full text |Cite
|
Sign up to set email alerts
|

The anti-inflammatory effects of baicalin through suppression of NLRP3 inflammasome pathway in LPS-challenged piglet mononuclear phagocytes

Abstract: In this study, the anti-inflammatory effects and mechanisms of baicalin on LPS-induced NLRP3 inflammatory pathway were investigated in piglet mononuclear phagocytes (control, LPS stimulation, LPS stimulation + 12.5 µg/ml baicalin, LPS stimulation + 25 µg/ml baicalin, LPS stimulation + 50 µg/ml baicalin and LPS stimulation + 100 µg/ml baicalin). The levels of reactive oxygen species (ROS), the secretion levels of IL-1β, IL-18 and TNF-α, mRNA expression levels of IL-1β, IL-18, TNF-α and NLRP3, as well as the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 32 publications
2
32
0
Order By: Relevance
“…Baicalin, one of the flavonoid compounds, is a major active ingredient in Chinese medicinal plant Radix Scutellariae (Huangqin). 7) Baicalin has various pharmacological activities, such as anti-inflammation, anti-oxidation, anti-cancer and anti-viral. [8][9][10][11] Previous study has revealed that baicalin has anti-adipogenic effect, anti-oxidation and anti-inflammatory effect in AS.…”
Section: Introductionmentioning
confidence: 99%
“…Baicalin, one of the flavonoid compounds, is a major active ingredient in Chinese medicinal plant Radix Scutellariae (Huangqin). 7) Baicalin has various pharmacological activities, such as anti-inflammation, anti-oxidation, anti-cancer and anti-viral. [8][9][10][11] Previous study has revealed that baicalin has anti-adipogenic effect, anti-oxidation and anti-inflammatory effect in AS.…”
Section: Introductionmentioning
confidence: 99%
“…Anti-in ammatory effects of baicalin in vitro and in vivo have been reported before [9,10]. In this study, we investigated whether baicalin affected the expression of pro-in ammatory cytokines and IFN-β in virus-infected CEF cells.…”
Section: No Effect Of Baicalin On Pro-in Ammatory Cytokines and Ifn-βmentioning
confidence: 99%
“…We have previously demonstrated that the anti‐inflammatory effects of baicalin are mediated through the suppression of the NLRP3 inflammasome pathway in a lipopolysaccharide (LPS)‐challenged piglet mononuclear phagocyte model (Ye et al, ). Baicalin also suppresses the secretion of the inflammatory cytokines and HMGB1 via NF‐κB and NLRP3 signaling in Haemophilus parasuis (HPS)‐stimulated piglet cells (Fu, Liu, Chen, et al, ; Fu, Liu, Xu, et al, ; Fu et al, ).…”
Section: Pharmacokinetic Parameters Of Baicalin Following Single Intrmentioning
confidence: 99%